Frustrations and roadblocks in data reference librarianship - Kubas, Alicia; McBurney, Jenny (IASSIST quarterly, 2019)
As data skills are incorporated into academic curriculum and data becomes more widely available and used in everyday life, many librarians find themselves serving as 'accidental' data librarians in their subject areas. Due to this evolving landscape and growing data need, it is increasingly important for librarians to be familiar with data resources and able to answer secondary data reference questions. To learn more about this area of librarianship, this study uses survey responses from librarians who answer data questions to explore the challenges and frustrations that arise from data reference questions and interactions. Our key findings reveal that frustrations are ever present in data reference regardless of how much experience a librarian has, and many frustrations arise due to factors such as patron expectations, subject-specific and data-related jargon, and data formats and accessibility.